2014
DOI: 10.1038/srep04398
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of the vaginal microbiome in HIV positive women using massive parallel semiconductor sequencing

Abstract: Infections by HIV increase the risk of acquiring secondary viral and bacterial infections and methods are needed to determine the spectrum of co-infections for proper treatment. We used rolling circle amplification (RCA) and Ion Proton sequencing to investigate the vaginal microbiome of 20 HIV positive women from South Africa. A total of 46 different human papillomavirus (HPV) types were found, many of which are not detected by existing genotyping assays. Moreover, the complete genomes of two novel HPV types w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
6
26
0
1
Order By: Relevance
“…The IVF category with its mixed flora is largely uncharacterised and complicates clinical approaches; IVF is however equally associated with poor obstetric outcomes and HIV as BVF, and has a profile more similar to that of BV than that of NVF 5 19 25. Although G. vaginalis was not significantly associated with HIV infection in our study, this species was abundant in HIV-positive women (77.8%), corresponding to previous findings in a similar population 26. The higher median concentrations of A. vaginae and G. vaginalis in HIV-positive women might contribute substantially to the spread of HIV, as these two species have been shown to induce and/or enhance the expression of HIV in vitro 27 28…”
Section: Discussionsupporting
confidence: 79%
“…The IVF category with its mixed flora is largely uncharacterised and complicates clinical approaches; IVF is however equally associated with poor obstetric outcomes and HIV as BVF, and has a profile more similar to that of BV than that of NVF 5 19 25. Although G. vaginalis was not significantly associated with HIV infection in our study, this species was abundant in HIV-positive women (77.8%), corresponding to previous findings in a similar population 26. The higher median concentrations of A. vaginae and G. vaginalis in HIV-positive women might contribute substantially to the spread of HIV, as these two species have been shown to induce and/or enhance the expression of HIV in vitro 27 28…”
Section: Discussionsupporting
confidence: 79%
“…In the present study we found that they were unable to establish a detectable colonization in the normal proximal gut but the resistance to their colonization disappeared when the CD4 counts dropped to below the normal limit in HIV infection. The bacteria do not seem related to oral sex as they were not present in the oral cavity as shown in the present study and were not reported to be present in the vagina by previous studies [2931]. A food or environmental contaminant was unlikely as all subjects including both HIV-infected patients and HIV-negative controls were from New York metropolitan area.…”
Section: Discussionsupporting
confidence: 39%
“…Clinically, our knowledge of opportunistic pathogens in relation to HIV-related proximal gut problems is rather limited, and clinical signs and symptoms alone rarely suggest a specific etiology. Besides the distal gut microbiome, high-throughput sequencing has been used to examine the effects of HIV infection on the microbiomes in the vagina [2931], lung [32], mouth [33, 34], Semen [35], and anus [36] as well as in normally sterile body sites such as the brain [37] and blood [38, 39], but not in the proximal gut. Unlike its distal counterpart, the status of microbiome in the proximal gut in HIV infection was only examined recently by analysis of gastric juice samples from only two HIV patients [40].…”
Section: Introductionmentioning
confidence: 99%
“…The sequences for HPV-x and HPV-y were obtained from the original authors32. Papillomaviruses are officially classified into distinct species by the International Committee for the Taxonomy of Viruses (ICTV)18.…”
Section: Methodsmentioning
confidence: 99%